The Absence of The Hero in Passagem De Humaitá by Victor Meirelles De Lima - Barros, Aldeir Isael Faxina; Albernaz, Cássio Alan Abreu (Revista de Historia Social y de las Mentalidades, 2023)
This paper analyses the pictorial work Passagem de Humaitá (1868-1872) by Victor Meirelles (1832-1903), starting from the perceived divergence with the other works of the same author, mainly, regarding the absence of the representation of the hero figure. The aim is to identify the relationships between the historical context and the pictorial representation, focusing on the possible political conflicts of interest that the author may have encountered and that somehow had an impact on the composition of the canvas. As support, we analyzed the bibliography on the artist sought, mobilizing together with contemporary periodicals the events represented and the presentation and reception of the canvas, in addition to similar works by other painters.
Keywords: Historical Painting; History of Brazilian Art of the 19th Century; War of the Triple Alliance Against Paraguay; Victor Meirelles de Lima